2018
DOI: 10.1021/acsphotonics.8b00814
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroadband near-Infrared Photoemission from Bismuth-Centers in Nitridated Oxide Glasses and Optical Fiber

Abstract: Wideband NIR-emitting materials are crucial components in light sources and tunable lasers for sensing, metrology, and optical amplification. While traditional rare-earth (RE) doped gain media have reached their limit in bandwidth, Bismuth-doped glasses have been evolving as an interesting alternative with unmatched spectral performance. However, serious issues remain for this type of material, in particular, in achieving the desired spectral bandwidth while providing the ability of fiber drawing on part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 57 publications
0
42
0
Order By: Relevance
“…Studies have shown that Bi 3+ acted as an excellent sensitizer ion to enhance the luminescence intensity of activator. Moreover, it provides broadband emission from UV‐Vis‐NIR and presents huge potential in fields of lighting, laser, and amplifier . The spectroscopic property of Mn 4+ was susceptible to surroundings in an octahedral host and its thermal response was dependent on its crystal lattice and tunable energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Bi 3+ acted as an excellent sensitizer ion to enhance the luminescence intensity of activator. Moreover, it provides broadband emission from UV‐Vis‐NIR and presents huge potential in fields of lighting, laser, and amplifier . The spectroscopic property of Mn 4+ was susceptible to surroundings in an octahedral host and its thermal response was dependent on its crystal lattice and tunable energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…34 Figure 2 gives the Raman spectra of the glass samples to further explain the structural changes. According to previous reports, 16,27 the broadband centered at 340 cm −1 is assigned to Gd/La-O − stretching vibration modes (nonbridging oxygen), whereas the band at 554 cm −1 is associated with symmetric stretching vibrations of Ge-O-Ge in six-GeO 4 Ge-O-Ge linkage increases gradually, and it then decreases when further increasing Bi 2 O 3 concentration; while the vibration intensity of B-O bonds in both BO 4 units and boroxol rings change in the opposite trend. As well-known, Bi 2 O 3 normally acts as a network modifier in multicomponent glass structure.…”
Section: F I G U R E 1 Transmission Spectra Of the Host And Gbxmentioning
confidence: 69%
“…In addition, bismuth‐doped or ‐based materials present unique photoluminescence features, because Bi 3+ can function as both an activator and a sensitizer. Typically, Bi‐doped materials can be developed as phosphors to radiate from UV to IR region . Therefore, in this paper, we have studied Eu 3+ ‐doped BNT ceramic in order to improve its electrical properties and achieve excellent luminescence properties …”
Section: Introductionmentioning
confidence: 99%
“…Typically, Bi-doped materials can be developed as phosphors to radiate from UV to IR region. [22][23][24][25] Therefore, in this paper, we have studied Eu 3+ -doped BNT ceramic in order to improve its electrical properties and achieve excellent luminescence properties. 17,[26][27][28][29][30][31] In this paper, ceramics containing different amounts of Eu 3+ ions were developed by the solid-state reaction method.…”
Section: Introductionmentioning
confidence: 99%